1996
DOI: 10.1017/s0730938400019584
|View full text |Cite
|
Sign up to set email alerts
|

Factors Considered by Ohio Juvenile Court Judges in Judicial Bypass Judgments: A Policy-Capturing Approach

Abstract: Judicial bypass is a procedure by which a minor can bypass notification of her parents to obtain an abortion if a judge finds her to be sufficiently mature. We examined the factors used by juvenile court judges in judicial bypass. Nine Ohio juvenile court judges indicated the likelihood of granting judicial bypass for 48 fictitious adolescents based on six factors relevant to each minor's maturity. Individual policies were calculated according to how each factor was weighed. The policies indicated that age, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It has also been used to investigate legal decisions made by judges in the American criminal justice system (e.g. Sensibaugh and Allgeier, 1996). Studies have typically investigated individuals' consistency in making decisions, agreement between different individuals' decisions on the same cases, their use of information, and their insight into their own policies.…”
Section: Judgment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been used to investigate legal decisions made by judges in the American criminal justice system (e.g. Sensibaugh and Allgeier, 1996). Studies have typically investigated individuals' consistency in making decisions, agreement between different individuals' decisions on the same cases, their use of information, and their insight into their own policies.…”
Section: Judgment Analysismentioning
confidence: 99%
“…Ebbesen and Konecni, 1975;Sensibaugh and Allgeier, 1996) and studies of jury decision making (e.g. Klevorick et al, 1984;Pennington and Hastie, 1981).…”
mentioning
confidence: 99%
“…Less commonly, but more appropriately, some researchers have followed the idiographic tradition and examined the decision-making of individual judges making decisions over multiple cases (e.g., Konečni & Ebbesen, 1984;Sensibaugh & Allegeier, 1996). However, when…”
Section: 'Researchers Analyzed Data Aggregated Over Groups Of Judges mentioning
confidence: 99%
“…For instance, an experimental study of nine Ohio juvenile court judges used regression models to capture their decision policies. Results revealed that only two to four statistically significant cues (out of a possible six) were used in their decisions about judicial bypass (Sensibaugh & Allgeier, ). The implication for forensic report writers is that not all information presented in expert reports will be considered.…”
Section: Evidence‐based Approaches To Forensic Report Writingmentioning
confidence: 99%
“…Results of research comparing judgements by different judges have typically yielded low rates of inter‐individual consistency. For instance, Sensibaugh and Allgeier () found that their nine judges agreed on the decision outcome in only one third of the cases; Dhami and Ayton () found that legal decision‐makers in their sample disagreed with the modal decision in an average of 15 (out of 27) cases.…”
Section: Evidence‐based Approaches To Forensic Report Writingmentioning
confidence: 99%